TOTAL QUALITY MANAGEMENT (TQM) DAN PENGARUHNYA TERHADAP KINERJA KARYAWAN (Studi Pada PT. Pos Indonesia Cabang Sumedang) - Istiono, Deni; Kurniasih, Nining (Jurnal Akuntansi Kompetif, 2023)
The purpose of this research is to investigate the effect of TQM practices implementation which consists of leadership, strategic planning, customer focus, information and analysis, people management, and process management on employee performance at PT. POS Indonesia. The population were 540 employees and 270 employees as respondent. The sample obtained based on simple random sampling method. Both descriptive statistic and Structural Equation Modelling (SEM) were employed to test the effect among variables. Data processing were used by SPSS and AMOS 16.00. The finding of research indicates that: TQM practices implementation which consists of leadership, strategic planning, customer focus, information and analysis, people management, and process management have significantly and positive effect on employee performance.